IMPROVING STUDENTS' READING COMPREHENSION OF NARRATIVE TEXTS THROUGH LISTEN-READ-DISCUSS (LRD) STRATEGY - Ni Putu Deni Milliana Putri; Sarah Kamagi; Fridolin Kukus (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
This study aims to determine whether or not students' reading comprehension of narrative texts may be improved by using the Listen-Read-Discuss strategy. A comprehension technique called the Listen-Read-Discuss (LRD) Strategy helps pupils increase their background knowledge before reading a material. The subject for this research is the class XI MIA 1 students of SMA Swadharma Werdhi Agung, which consists of 30 students. The researcher employed quantitative research using pre-experimental design with one group pre-test and post-test designs. A multiple-choice exam was the research tool employed in this study. The mean score method was used to statistically analyze the research's data. The results of the students' pre-test and post-test were 53 and 80, respectively, when the data were computed. Between the Pre-test and Post-test, the students' scores varied by 27, on average. According to the study's findings, the post-mean test's score was greater than the pre- test's. As a consequence, teaching reading comprehension for narrative texts using the Listen-Read-Discuss (LRD) Strategy was very successful in raising the students' mean score for reading comprehension for narrative texts